Draft Annual Plan 2012-13 Vol. I Union Territory of Lakshadweep - Planning Commission (Planning Commission, 2012)
Lakshadweep- the tiniest Union Territory of India, is an archipelago consisting of 12 attols, 3 reefs and 6 newly formed/ submerged sand banks Comprised of - 11 inhabited islands, 16 uninhabited islands; six newly formed / submerged sand banks and 3 reefs.
Union Territory of Lakshadweep